2023
DOI: 10.1021/acsnano.2c08776
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Degradation during Intercalation and Alloying in Batteries

Abstract: Numerous layered materials are being recognized as promising candidates for high-performance alkali-ion battery anodes, but black phosphorus (BP) has received particular attention. This is due to its high specific capacity, due to a mixed alkali-ion storage mechanism (intercalation-alloying), and fast alkali-ion transport within its layers. Unfortunately, BP based batteries are also commonly associated with serious irreversible losses and poor cycling stability. This is known to be linked to alloying, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…24,33 Given the expansion/layer shearing of the BP framework upon charging, it is assumed that some of the strain effects on the BP crystal from intercalation of Li remain after the crystal is discharged with PhCN, which would be concurrent with some P–P bond weakening, consistent with work by Karki et al , 32 and shown recently from ex situ Raman spectroscopy of BP electrodes electrochemically intercalated and de-intercalated with Na. 34…”
Section: Resultsmentioning
confidence: 99%
“…24,33 Given the expansion/layer shearing of the BP framework upon charging, it is assumed that some of the strain effects on the BP crystal from intercalation of Li remain after the crystal is discharged with PhCN, which would be concurrent with some P–P bond weakening, consistent with work by Karki et al , 32 and shown recently from ex situ Raman spectroscopy of BP electrodes electrochemically intercalated and de-intercalated with Na. 34…”
Section: Resultsmentioning
confidence: 99%
“…67 Moreover, the Raman peak of the pure Si electrode has a more significant downshift and a more increased full width at half-maximum than that of Si@FeNO@P after the cycles, indicating worse structural stability. 68 The chemical states of the Si and Si@FeNO@P electrodes before and after 50 cycles were further investigated, as revealed in Fig. 7d.…”
Section: Resultsmentioning
confidence: 99%
“…67 Moreover, the Raman peak of the pure Si electrode has a more significant downshift and a more increased full width at half-maximum than that of Si@FeNO@P after the cycles, indicating worse structural stability. 68…”
Section: Resultsmentioning
confidence: 99%
“…However, as the state-of-charge (SOC) progresses (Mg loading), BP experiences substantial volumetric expansion, leading to the disruption of P–P bonds within layers . Both theoretical and experimental studies have indicated that the origin of such structural breakdown of BP anode is the Mg–P alloying at high SOC. This phenomenon results in poor rate performance and reduced cycling efficiency for the BP anode …”
Section: Introductionmentioning
confidence: 99%
“…Notably, orthorhombic black phosphorus (BP), which is the thermodynamically most stable allotrope of phosphorus under ambient conditions, stands out due to its puckered layered structure. , BP exhibits similar intercalation chemistry to graphite, but with a corrugated interlayer spacing that can accommodate Mg-ions, offering significant storage capacity at sufficiently low potential . However, as the state-of-charge (SOC) progresses (Mg loading), BP experiences substantial volumetric expansion, leading to the disruption of P–P bonds within layers . Both theoretical and experimental studies have indicated that the origin of such structural breakdown of BP anode is the Mg–P alloying at high SOC.…”
Section: Introductionmentioning
confidence: 99%